KEBERADAAN MOGOK KERJA DALAM KONSTELASI HUBUNGAN INDUSTRIAL PANCASILA - Widiastiani, Nindry Sulistya (Penerbit Universitas Atma Jaya Yogyakarta, 2017)
Indonesia’s industrial relations is called the Pancasila industrial relations, which requires a harmonic situation between the labor and the employer. On the other hand, the Pancasila industrial relations also contains the conflict concept which appears in the existence of labor strike. However, the conflict concept in the existence of labor strike is in line with the Pancasila industrial relations’ harmonic concept. The labor strike is the part of industrial relations dispute settlement, which is not to undermining the Pancasila industrial relations’ harmonic concept. The right to strike is given to the labor for increasing their bargaining power when the industrial relation dispute arises. The existence of labor strike actually become a means to restore the harmonic situation when the industrial relation dispute arises.Keywords: industrial relations, the Pancasila industrial relations, labor strikeIntisariHubungan industrial di Indonesia merupakan hubungan industrial Pancasila, yang menghendaki situasi yang harmonis antara pekerja dengan pengusaha. Di sisi lain, hubungan industrial Pancasila juga mengakomodasi konsep konflik yang tercermin dalam keberadaan mogok kerja. Keberadaan mogok kerja yang mengandung konsep konflik sejatinya tidak bertentangan dengan konsep keharmonisan dalam hubungan industrial Pancasila. Mogokkerja dihadirkan sedemikian rupa sebagai salah satu upaya penyelesaian perselisihan hubungan industrial, tidak dimaksudkan untuk merusak tatanan keharmonisan sebagaimana dicita-citakan oleh hubungan industrial Pancasila. Hak mogok kerja diberikan kepada pekerja digunakan untuk membantu menyeimbangkan posisi tawar pekerja saat terjadi perselisihan hubungan industrial. Keberadaan mogok kerja sejatinya merupakan saranauntuk mengembalikan keharmonisan di saat terjadi konflik dan perselisihan dalam hubungan industrial.Kata kunci: hubungan industrial, hubungan industrial Pancasila, mogok kerja.